Effective practices in trade finance examinations. (ADB briefs., 2019)
Drawing from the experiences of bank regulators and commercial banks, the brief aims to provide a better understanding of trade finance and how departments involved work. It is also intended to advance alignment in examination practices and international standards on AML-CFT regulation and activities.